Significance of Prescribing Astigmatic Correction in Young Patients having Low Astigmatism with Near Vision Complaints : Astigmatic Correction in Young Patients having Low Astigmatism - Rashid, Faisal; Chaudhary, Muhammad Ajmal; Khan, Nasrullah; Iqbal, Rana Naveed; Waheed, Mustafa Khalid; Khan, Asad Aslam (Pakistan Journal of Health Sciences, 2023)
Astigmatism causes increased difficulty in reading performance like book reading, mobile usage and computer work. Objective: The primary objective was to find out the significance of prescribing astigmatic correction in young patients having low astigmatism with near vision complaints and secondary objective was to find out the most common type of astigmatism affecting near vision. Methods: This was a multicentered, prospective cohort study conducted from April 2022 to Sep 2022. A total of 64 subjects of both genders were selected through non-probability convenient sampling technique. Patients with age between 15-30 years having low astigmatism (0.25-0.75D) with near vision complaints were included. Any amount of astigmatism was corrected with appropriate glasses and subjects were asked for a follow up fortnightly. Follow up improvement in symptoms were recorded and compared with earlier complaints by applying chi square test using SPSS version 23.0. Results: A total of 64 subjects were enrolled in the study. The mean age of patients was 22.44 years including 27 (42%) males and 37 (58%) females. The most common symptom was Eye Strain found in 53 (83%) of the patients. Most common type of astigmatism was Against the Rule astigmatism. 62 (96%) patients improved to 6/6 in both eyes. On follow up, improvement in symptoms was noted and compared with symptoms before the usage of glasses. Conclusions: The study concluded that the treatment for near vision complaints in young patients is prescribing them with proper cylindrical / astigmatic correction in the form of eye glasses.